2020
DOI: 10.1159/000507631
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the Peripheral Blood Mononuclear Cell Proteome in Schizophrenia and Mood Disorders for the Discovery of Discriminatory Biomarkers: A Proof-of-Concept Study

Abstract: Introduction: Current diagnoses in psychiatry are solely based on the evaluation of clinical presentation by the treating psychiatrist. This results in a high percentage of misdiagnosis and consequential inefficient treatment; especially regarding major depressive disorder (MDD), depression in the context of bipolar disorder (BD-D), bipolar disorder with manic symptoms (BD-M), and psychosis in the context of schizophrenia (SZ). Objective biomarkers allowing for accurate discriminatory diagnostics are therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It is known from the literature that brain metabolites are used as valuable predictors differentiating schizophrenia from bipolar disorder. In the study by Coppens et al, nuclear magnetic resonance spectroscopy (MRS) was used to search for specific central biomarkers differentiating these two diseases [ 38 ]. The metabolites typical for schizophrenia were gamma-aminobutyric acid (GABA), isovaleryl carnitine, mannitol, and pantothenate, while in patients with bipolar disorder they were 2,3-diphospho- d -glyceric acid, monoethylmalonate, and N -acetyl aspartylglutamic acid [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known from the literature that brain metabolites are used as valuable predictors differentiating schizophrenia from bipolar disorder. In the study by Coppens et al, nuclear magnetic resonance spectroscopy (MRS) was used to search for specific central biomarkers differentiating these two diseases [ 38 ]. The metabolites typical for schizophrenia were gamma-aminobutyric acid (GABA), isovaleryl carnitine, mannitol, and pantothenate, while in patients with bipolar disorder they were 2,3-diphospho- d -glyceric acid, monoethylmalonate, and N -acetyl aspartylglutamic acid [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, a total of 14 studies were identified in BD and Table 1 gives an overview of these studies ( Table 1 ). 50 51 52 53 54 55 56 57 58 59 60 61 62 63 Fig. 1 is the flow diagram of the search strategy adopted during the writing of this section of the manuscript ( Fig.…”
Section: Proteomic Biomarkersmentioning
confidence: 99%